Independence day - Devlin, Dean; Emmerich, Roland; Devlin, Dean; Goldblum, Jeff; Mc Donnell, Mary; Pullmen, Bill; Smith, Will (New York : Twentieth Century Fox Film Cop., 1996)
'Powerful aliens launch an invasion against the human race. The world's only hope lies with determined survivors, uniting for one last strike against the invaders, before its the end of mankind' Container
1 film reel : sd., col. ; 3/4
Keywords: Science fiction films